Optimum Trade Restrictions and Their Consequences - Thurow, Lester C.; White, Halbert (Econometrica, 1976)
[This paper develops a simulation model to study the income distribution effects–total and factorial-of optimum restrictions on the flows of factors and products across national boundaries. Imposing both optimum tariffs and optimum taxes on factor flows allows an increase in national income that is much larger than the sum of the two effects evaluated separately. Often there are large shifts in the incomes of factors even though total income changes only slightly.]